Comparison of 2D and 3D modelling applied to single phase flow of nanofluid through corrugated channels - Kh. Abugnah, Elhadi; Wan Salim, Wan Saiful-Islam; M. Elfaghi, Abdulhafid; Ngali, Zamani (Semarak Ilmu, 2022)
Nanofluid flow through non-corrugated and corrugated channels is studied using a two-dimensional (2D) and three dimensions (3D) numerical simplification. Due to the high computational costs of a full 3D grid model, the 2D approach offer a more practical advantage. However, little information about its validity is available. The aim of this study is to explore to which extent 2D simulations can describe the flow within a 3D geometry, and to investigate how effective the commonly used 2D numerical simplification is in nanofluid flow through non-corrugated and corrugated channels. A case study has implemented with 2D and 3D mesh models to compare their results taking into consideration the analysis of heat transfer and pressure drop. A simulation has been carried out using Ansys fluent software to compare the results for different Reynolds Numbers ranges from 10000 to 30000 and different geometries noncorrugated, semicircle and rectangular channels. The results show that for noncorrugated channel there is a slight difference between 2D and 3D results for all Reynolds number ranges, while for both semicircle and rectangular corrugated channels, the difference becomes larger for high Reynold’s Number.